VALLINGS IN DIET OF CHILDREN WITH HYPOTROPHY OR UNSTABLE STOOL - G.A. Kulakova; E.A. Kurmayeva; N.A. Solov'eva; L.A. Morozova; E.V. Trofimenko ("Paediatrician" Publishers LLC, 2010)
Problem of nutritive status correction in children with body mass deficiency is still topical. Drug treatment is not efficient completely is no individual correction of nutrition is provided. Development of a diet should be performed taking into account peculiarities of infants with body mass deficiency. Correction of nutrition in 20 children with hypotrophy and 20 children with unstable stool was performed with Vallings - liquid homogeneous milk-cereal mixtures with high nutritive value and sparing consistence. Normalization of intestinal function and common increase of body mass was detected in one month after the beginning of treatment.Key words: children, hypotrophy, diarrhea syndrome, Vallings.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):117-122)